Physico-chemical characteristics of water samples of three barangays of Batan, Aklan. - De Guzman, Lucita C. (1992)
This study will give information to the residents of the barangay in Batan, Aklan if the water is good for irrigation purposes, specifically for pineapple.
Terminal report-CFOS
Keywords: Water samples of Batan, Aklan